Design and Characterization of an Intracellular Covalent Ligand for CC Chemokine Receptor 2 - Ortiz Zacarías, Natalia V. (J Med Chem, 2021)
[Image: see text] Covalently acting inhibitors constitute a large and growing fraction of approved small-molecule therapeutics as well as useful tools for a variety of in vitro and in vivo applications. Here, we aimed to develop a covalent antagonist of CC chemokine receptor 2 (CCR2), a class A GPCR that has been pursued as a therapeutic target in inflammation and immuno-oncology. Based on a known intracellularly binding CCR2 antagonist, several covalent derivatives were synthesized and characterized by radioligand binding and functional assays. These studies revealed compound 14 as an intracellular covalent ligand for CCR2. In silico modeling followed by site-directed mutagenesis confirmed that 14 forms a covalent bond with one of three proximal cysteine residues, which can be engaged interchangeably. To our knowledge, compound 14 represents the first covalent ligand reported for CCR2. Due to its unique properties, it may represent a promising tool for ongoing and future studies of CCR2 pharmacology.